Pilots' Monument, Yellowknife -- photograph ... - Seale, Linda N. (University of Alberta Library, 2011)
Historic marker on Pilots' Monument ('The Rock') in the Old Town area of Yellowknife, NT. The Monument is a high point that originally held the town water tanks but is now dedicated to the bush pilots and air engineers. In summer the monument has a signal light on top that flashes when a float plane is about to land on the adjacent channel, indicating that boat traffic should move aside. Photograph taken January 2011. ...